Design and fabrication method for Biomedical apparatus using computer aided method and rapid prototyping machine - Yupiter HP, Manurung; Asli, Kasim; Mohd Zaim Zulkaisi, Ghazali; Shaharudin, Ahmad; Mohd Reza, Dollah Sajat; Shahidan, Mohamad; Mohd Fadeli, Muhammad Salleh (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.